Vishva Dixit Shares Insights on His Early Influences, Research Career, Key Findings, and What it Takes to Be Successful in Science - Neil S. Greenspan (Case Western Reserve University, 2023)
In this interview, Vishva Dixit, MD, talks with Neil S. Greenspan, MD, PhD, senior editor of Pathogens and Immunity aboutwhat his career in science has revealed about biology in humans, but also what it has revealed about how to be successful in science. Dr. Dixit is a world-famous immunologist and biochemist who has made major contributions to the study of innate immunity in general and particularly to understanding inflammasome activation. He is vice president and senior fellow in physiological chemistry at Genentech.